The ultimate question 2.0 : - Reichheld, Fred (Harvard Business Press, 2011)
In this thoroughly updated and expanded edition, Reichheld, with Bain colleague Rob Markey, explains how practitioners have built Net Promoter into a full-fledged management system that drives extraordinary financial and competitive results. With his trademark clarity, Reichheld: Defines the fundamental concept of Net Promoter, explaining its connection to your company's growth and sustained success, Presents the closed-loop feedback process and demonstrates its power to energize employees and delight customers, Shares new and compelling stories of companies that have transformed their performance by putting Net Promoter at the center of their business Practical and insightful, The Ultimate Question 2.0 provides a blueprint for long-term growth and success